1975
DOI: 10.1159/000175595
|View full text |Cite
|
Sign up to set email alerts
|

Bulking Agents in the Treatment of Obesity

Abstract: The effect of two bulk-forming appetite depressants, methylcellulose and gum guar, on food intake has been studied in 11 (4 male, 7 female) healthy volunteers – 3 of whom were overweight. 10 g of active ingredient were given in two equal doses daily for periods of 1 week for each agent. Individually weighed dietary intakes were obtained over four consecutive weeks; the first and third weeks were without medication. Both gum guar and methylcellulose were equally effective in reducing appetite by 10 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 4 publications
3
26
0
1
Order By: Relevance
“…48 It is believed that dietary fibers, including glucomannan, may provoke body weight loss by acting as bulking agents, thereby increasing satiety and reducing caloric intake, ingestion rate, and nutrient absorption. [29][30][31][32][33] Glucomannan is a highly viscous fiber, more so than pectin and 5-fold more than guar gum. 49 Due to this high viscosity, glucomannan has been reported to decrease the postprandial increase in blood glucose and insulin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 It is believed that dietary fibers, including glucomannan, may provoke body weight loss by acting as bulking agents, thereby increasing satiety and reducing caloric intake, ingestion rate, and nutrient absorption. [29][30][31][32][33] Glucomannan is a highly viscous fiber, more so than pectin and 5-fold more than guar gum. 49 Due to this high viscosity, glucomannan has been reported to decrease the postprandial increase in blood glucose and insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…This supplement was standardized to contain a novel blend of glucomannan, chitosan, fenugreek, Gymnema sylvestre, and vitamin C. It is believed that dietary fibers such as glucomannan may provoke body weight and fat loss by acting as a bulking agent, thereby increasing satiety and reducing caloric intake, ingestion rate, and nutrient absorption. [29][30][31][32][33] Chitosan is a unique, indigestible, nonplant fiber that may aid in body weight loss by reducing fat absorption in the intestinal tract. The addition of ascorbic acid to chitosan has been shown to improve the ability of chitosan to bind to dietary fats and inhibit their digestion.…”
Section: Introductionmentioning
confidence: 99%
“…With long-term supplementation of NUTRIOSE s FB, also effects of dietary fibre (soluble and insoluble) on body weight (BW) and body composition may be of interest. After fibre consumption, flattening of blood levels of insulin and glucose have been reported, resulting in decreased appetite (Albrink, 1978;Hamilton and Anderson, 1992;Rössner, 1992) and less food intake (Evans and Miller, 1975;Levine et al, 1989;Cybulski et al, 1992;DeLargy et al, 1995;Pasman et al, 1997). It is therefore interesting whether NUTRIOSE s FB in the long term, by reducing energy intake, affects body weight and body composition.…”
Section: Introductionmentioning
confidence: 99%
“…Bulking supplements such as dietary fibre increase feelings of fullness (Evans & Miller, 1975;Leeds, 1987;Raben, Christensen, Holst & Astrup, 1994) and augment satiating effects (Spiller, 1993;Ryttig, Tellnes, Haegh, Boe & Fagerthun, 1989) and so reduce energy intake and body weight. Interventions with a high and low fibre meal, short-term and long-term interventions (breakfast-Burley, Leeds & Blundell, 1987;breakfast-Delargy, Burley, O'Sullivan, Fletcher & Blundell, 1995;all mealsDuncan, Bacon & Weinsier, 1983; pre-loads before meals- Porikos & Hagamen, 1986;van der Ven et al, 1994;long-term supplementation-Ryttig et al, 1989;Rigaud et al, 1990;Krotkiewski, 1984) all showed decreased hunger feelings and decreased energy intake when fibre was added.…”
mentioning
confidence: 99%